2017
DOI: 10.4317/medoral.21556
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to change of the duration of consolidation period in the distraction osteogenesis with the repetition of extracorporeal shock waves?

Abstract: BackgroundIn this study we examined the effects of two different repeated Extracorporeal Shock Waves (ESW) on the consolidation period of the distraction osteogenesis (DO) of the rabbit mandible using stereological, radiological and immunohistochemical methods.Material and MethodsDO was performed unilaterally in the mandible of 18 New Zealand rabbits (six months old, weighing between 2.5-3 kg). In the consolidation period, rabbits were divided into three groups randomly after the distraction period. The distra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…In this context, the points falling on the area of interest were counted and the total number (Σp) was obtained. The obtained numbers were multiplied by a (p) to achieve surface area (A) measurements for ovarian volume, cortex/medulla ratio and follicle volume [14].…”
Section: Cavalieri Methodsmentioning
confidence: 99%
“…In this context, the points falling on the area of interest were counted and the total number (Σp) was obtained. The obtained numbers were multiplied by a (p) to achieve surface area (A) measurements for ovarian volume, cortex/medulla ratio and follicle volume [14].…”
Section: Cavalieri Methodsmentioning
confidence: 99%
“…Only Önger et al (12) performed a second session on the fourth day of the consolidation. Whereas Lai et al (17) reported that a 500 pulse shock wave therapy with an energy flow density of 0.19 mJ/mm2 is effective in increasing angiogenesis and bone regeneration and in shortening the consolidation process, Önger et al(12) showed that a 1,000 x2 pulse shock wave therapy at an energy flux density of 0.19 mJ/ mm2 resulted in a higher new bone volume and bone mineral density. Lai et al (17) also found that shock waves applied at 21 kV and 500 pulses caused necrotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ESWT has this effect by triggering the expression of transcription factors, mediators, and growth hormones (13,14, 15). ESWT has also been reported to induce mesenchymal cell proliferation and differentiation, and to promote osteogenesis by stimulating osteoblasts (12,13,15,16). These effects have been shown to induce open fracture healing, shorten consolidation period in DO, and increase bone mineral density (12,17).…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods to promote callus formation have been reported. These attempts include; bisphosphonates, thrombocyterich plasma, hormones, demineralized bone matrix, calcium sulphate, electrophysiological applications, low-intensity laser, growth factors, shock waves, ultrasound, hyperbaric oxygen, bone grafts, cytokines, stem cells 5,6 . However, there are no sufficient studies on the effects of ESWT on the new bone formation in DO in the maxillofacial area.…”
Section: Distraction Osteogenesismentioning
confidence: 99%
“…ESWT was first used in the maxillofacial area after the 1990s, in the treatment of sialolithiasis 2,3 . Later on, studies on mandibular distraction osteogenesis, fracture and defect healing, acceleration of orthodontic tooth movement and alveolar bone regeneration surged [4][5][6] . Experimental and clinical studies have confirmed that shock waves have different dose dependent biological and mechanical effects on each tissue 7 .…”
Section: Introductionmentioning
confidence: 99%